Parasitic performance of Trichogramma japonicum Ashmead on eggs of rice moth and rice stem borer : a comparative study - Mohapatra, Bikash; Shinde, CU; Jena, Manoj Kumar (ORYZA-An International Journal of Rice, 2023)
The present investigation on the parasitic potential of T. japonicum was undertaken during the year 2019-20 at the Bio-control Laboratory, Department of Agricultural Entomology, Navsari Agricultural University, Navsari (Gujarat). The results showed that the parasitic potential (F0) of T. japonicum was maximum (82.65 ± 6.86%) on Corcyra eggs as compared to rice yellow stem borer eggs (24.11 ± 3.37%). Similarly, the egg parasitization (F1) of T. japonicum on Corcyra eggs was comparatively higher (83.15 ± 5.06%) than that on yellow stem borer eggs (25.68 ± 3.60%). Moreover, the observed difference in parasitic potential of T. japonicum on Corcyra and Scirpophaga incertulas for both generations was found highly significant during the present investigation. The conclusion of the present investigation suggested that the natural host, the Yellow Stem Borer (YSB), could serve as a viable means for recycling the nucleus culture as well as amplifying the parasitic capabilities of T. japonicum during mass production program. Moreover, these findings could hold significant value in assessing the parasitic behavior of YSB when T. japonicum is introduced into paddy fields.